The Meaning of ʾÔpan in Proverbs 20.26. Issue 3 (December 2016) - Amzallag, Nissim; Yona, Shamir
Proverbs 20.26 allegorizes the optimal method of scattering the wicked by likening it to the wind-driven separation of chaff from grain. Since the word ʾ ôpan denotes the tool used for this process, it is proposed here that this term evokes a tuyere, a nozzle through which air is forced in a furnace, rather than a cartwheel, used for the threshing of grain. Functional affinities between ʾ ôpan and ʾ ap (= nose), the organ of blowing, together with the lack of a satisfying etymology for ʾ ôpan as a wheel, suggest that tuyere is the primary meaning of this noun in ancient Canaanite languages. Moreover, the similarity of ancient furnace nozzles to spokeless wheels suggests that the use of ʾ ôpan to denote a wheel is derived from the primary denotation of the word, a tuyere.